2018
DOI: 10.1093/mnras/sty2456
|View full text |Cite
|
Sign up to set email alerts
|

Optical and X-ray observational search for the possible supernova remnant candidates in the nearby galaxy NGC 1569

Abstract: We report the results of our investigation on the possible existence of supernova remnants (SNRs) in the nearby galaxy, NGC 1569, using the CCD imaging and spectroscopic observations from the RTT150 telescope of TUG-TUBITAK in Antalya, Turkey for two different observing periods. Using [S ii]/Hα ≥ 0.4 standard criteria, the identification of 13 new SNR candidates for this galaxy is proposed for two different epochs. We found the [S ii]/Hα ratios ranging from 0.46-0.84 and Hα intensities ranging from (2.2-32) × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…Regarding the expansion velocities, almost all SNRs present Vexp >100 ±1 km s −1 except SNRs 3, 7 and 8 with Vexp of 95 ±1, 90 ±1 and 87 ±1 km s −1 , respectively. The Vexp value of SNR5 (Vexp = 114 ±1 km s −1 ) is in agreement with the Vexp value reported by Ercan et al (2018).…”
Section: Expansion Velocity Of Snrssupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the expansion velocities, almost all SNRs present Vexp >100 ±1 km s −1 except SNRs 3, 7 and 8 with Vexp of 95 ±1, 90 ±1 and 87 ±1 km s −1 , respectively. The Vexp value of SNR5 (Vexp = 114 ±1 km s −1 ) is in agreement with the Vexp value reported by Ercan et al (2018).…”
Section: Expansion Velocity Of Snrssupporting
confidence: 91%
“…Recently, Ercan et al (2018) showed evidence of 13 possible optical SNRs candidates in this galaxy with CCD imaging using the [S ii]/Hα ≥ 0.4 standard criteria. They identified the new SNRs candidates and computed the electron density (ne), of about 121±17 cm −3 for only one SNR candidate using the [S ii]λ6716/[S ii]λ6731 average flux ratio.…”
Section: Snrs In Ngc 1569mentioning
confidence: 99%
“…[49], Buat et al [4] together with Neutral Hydrogen column density relation from Predehl and Schmitt [48]. This is similar to the determinations reported for another nearby galaxy by Ercan et al [14].…”
Section: Spectral Data Analysissupporting
confidence: 82%